Answer:
Step-by-step explanation:
y = -3x - 3
m = -3_______
b = -3________
y = 2x + 2
m = 2_______
b = _2_______
SOLVE NOW : -3x - 3 = 2x + 2
- 5x = 5
x = -1
subst in y : y = 2(-1)+2 = 0
the solution is : ( - 1 , 0 )
y = -3x- 3 an equation for the line 'red'
y = 2x+2 an equation for the line 'bleus'
A. 4times y+2 b. 5-x times 3 times y c. -2 times y-3 d. -7 times 4+x e. 16 times x -8 divided by 4 f. 1 divided by 3 times 2 times x +3
sorry I tried to make it out the best that I could I don't have all the symbols so I just wrote out the divide and multiply parts
5x-3=2.5x+x solve this equation that I just gave you for X then plug it in to 2.5x and that will equal MN
Answer:
Step-by-step explanation:
<em>Set up equations (L= Lisa; M = Maria; A = April; J = Jim)</em>
L = 12M
A = 2J
<em>Substitute x for Maria and 6x for Jim</em>
L = 12x
A = 2(6x) = 12x
<em>So, you get:</em>
Maria = x
Jim = 6x
Lisa = 12x
April = 12x